"I have to start learning how to live with becoming sick": A scoping review of the lived experiences of people with Huntington's disease. Issue 1 (13th July 2021) - Mahmood, Saadia; Law, Susan; Bombard, Yvonne
Abstract: Person‐centered care (PCC) is recognized as a key component of the delivery of quality healthcare and a model for healthcare systems worldwide. The experience of illness through a person's perspective is one domain defining PCC contributing to a growing interest in examining the lived experiences of illness. This scoping review sought to examine what is known from the existing literature about the lived experiences of persons gene‐positive for or living with Huntington's disease (HD) as described in their own voices and to outline prominent psychosocial themes of those experiences. Five databases were systematically searched and analyzed resulting in 19 publications for inclusion. Using a thematic analysis, five prominent psychosocial themes were identified: grappling with control, avoidance as an escape from realities, adaptation to new realities, managing emotions, and appreciation for life. Variation in themes existed across HD life stage of being undiagnosed or diagnosed with HD. The findings of this review demonstrate that individuals who are gene‐positive for or living with HD require support well beyond the disclosure of genetic testing and that it may be beneficial for healthcare providers to consider where along the life stage trajectory a person affected by HD may be to ensure the delivery of quality PCC. Abstract : "I have to start learning how to live with becoming sick": A scoping review of the lived experiences of people with Huntington's disease.